2014
DOI: 10.1371/journal.pone.0103063
|View full text |Cite
|
Sign up to set email alerts
|

MTHFR C677T Predisposes to POAG but Not to PACG in a North Indian Population: A Case Control Study

Abstract: Hyperhomocysteinemia induced by the C677T genetic variant in MTHFR (methylenetetrahydrofolate reductase) has been implicated in neuronal cell death of retinal ganglion cells (RGC), which is a characteristic feature of glaucoma. However, association of MTHFR C677T with glaucoma has been controversial because of inconsistent results across association studies. Association between MTHFR C677T and glaucoma has not been reported in Indian population. Therefore, with a focus on neurodegenerative death of RGC in glau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 33 publications
3
10
0
Order By: Relevance
“…Similar to our findings, no association of MTHFR C677T polymorphism has been found with the susceptibility to PACG in Nepalese and Australian [31], and Indian [15]. Contrary to these findings one report from Pakistan indicates that the MTHFR C677T polymorphism is associated with PACG.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Similar to our findings, no association of MTHFR C677T polymorphism has been found with the susceptibility to PACG in Nepalese and Australian [31], and Indian [15]. Contrary to these findings one report from Pakistan indicates that the MTHFR C677T polymorphism is associated with PACG.…”
Section: Discussionsupporting
confidence: 81%
“…The prevalence of MTHFR C677T polymorphism has been reported to be high in POAG patients [4, 14, 15]. However, earlier reports on the association between MTHFR C677T polymorphism and glaucoma risk are inconclusive and conflicting [6, 7, 16–20].…”
Section: Introductionmentioning
confidence: 99%
“…Rather this study found that this variant is associated with POAG. 84 This may suggest that the pathogenic effect of MTHFR mutations is primarily related to homocysteine toxicity leading to RGC loss, which is a characteristic feature of all types of glaucoma.…”
Section: Nebmentioning
confidence: 99%
“…Among the remaining studies, 84 articles were excluded because they were review articles, letters to editors, previous meta-analyses, not relevant to MTHFR C677T and A1298C, not casecontrol studies, evaluated other diseases instead of glaucoma, case reports, and other polymorphisms of MTHFR gene. Finally, a total of 42 case-control studies including 33 studies (in 19 publications) with 3,504 cases and 2,525 controls for MTHFR C677T [9][10][11][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] and nine studies (in six publications) with 1,073 cases and 775 controls for A1298C [11,[19][20][21]23,29] were selected. The main characteristics of studies included in the current meta-analysis are presented in Tables 1 and 2.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%